Pengembangan Bahan Ajar Berbasis Literasi Sains pada Materi Sistem Pencernaan Manusia - Rambe, Santi Ariani; Khairuna, Khairuna (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The scientific literacy understanding ability of Indonesian students according to PISA results from 2000 to 2012 shows that Indonesia continues to decline in rank. In 2015, Indonesia's PISA score has increased, although it increased, it is still much lower than the international average PISA 500 score. Teaching materials are one of the factors that affect students' understanding of scientific literacy. A balanced aspect of scientific literacy has not been fully incorporated into teaching materials in Indonesia. Therefore, it is necessary to develop balanced teaching materials for science. This study aims to determine the characteristics, feasibility, legibility, and improvement of students' scientific literacy. The research method used is research and development. The object of this research is SMP Karya Bunda. The sampling technique was carried out using a simple random sampling technique. The final product of this research is educational material that presents aspects of scientific literacy, namely science as knowledge, science as research, science as a mindset, and the interaction between science, technology, and society. The results of the feasibility test showed that the teaching materials met the criteria very well with a score of 87.98. The results of the readability test showed that the teaching materials used were easy to understand with average readability of 67%. The test results (victory test) showed that the average understanding of the experimental class's science understanding was 67.3%, while the control class was low at 30.8%. These results indicate differences in the improvement of scientific literacy between students who use technical materials and those who use ordinary materials in school.